Pilot study: assessing the clinical diagnosis of allergy in atopic children using a microarray assay in addition to skin prick testing and serum specific IgE. Issue 1 (December 2016) - Foong, Ru-Xin; Roberts, Graham; Fox, Adam; Toit, George
Abstract Background Children with atopic dermatitis (AD) are at risk of developing allergy. Alongside clinical history, testing modalities include skin prick tests (SPT), specific immunoglobulin-E (sp-IgE) and recently, microarray assays. The aim of this pilot study was to assess current tests and the ISAC sIgE-112 system in the diagnosis of food and aeroallergen allergy. Methods Children aged 0–11 years with moderate to severe AD were included. An initial allergy assessment including clinical history, SPT and sp-IgE was performed to determine food and aeroallergen sensitization. A second independent clinical assessment using the same information given to the first assessor and ISAC test results for food and aeroallergen sensitization was also made for each participant. The results from both were compared. Results 30 children [mean age 3.91 years (SD 3.3)] were included; 53.3 and 46.7 % had moderate and severe AD, respectively. Sp-IgE tests had a higher percentage of positive results compared to SPT and ISAC tests for common allergens. There was a significant difference between the three tests in detecting aeroallergen sensitization (p = 0.038), especially between sp-IgE and ISAC tests, but no significant difference between the tests for food allergen sensitization. There was good agreement between the two assessors; 70 % of the children had a change in diagnosis, with 60 % having at least one diagnosis added and 40 % having at least one diagnosis removed. Conclusions There is a role for the use of ISAC testing in diagnosing sensitization and allergy in children with AD as it leads to a change in diagnosis for many patients. Further work is required to assess its clinical and cost effectiveness.